The Influence Of Principal's Leadership Style And Organizational Culture On Teacher Performance At MA Unggulan Hikmatul Amanah - Enita Rosmika; Yuli Dwi Prastika; Ari Kartiko (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2022)
Leadership is an important factor in leading an organization because the leader determines the progress of the organization. This study aims to determine the effect of the principal's leadership style and organizational culture on teacher performance at the Hikmatul Amanah Supreme Court. This study uses quantitative research, the respondents are 40 teachers of Wisdom Amanah, the research instrument uses a Likert scale, the data collection technique uses a questionnaire while the data analysis technique uses multiple linear regression. The results show that: 1. Leadership style has no significant effect on performance. teacher at the Hikmatul Amanah Supreme Court with a t-count value of 0.828 and a significance value of 0.413.2. Organizational culture has a significant effect on teacher performance with a t-count value of 7.216 and a significance value of 0.000. 3. Simultaneously leadership style and organizational culture have a significant effect on teacher performance with a calculated F value of 28.796 and a significance value of F of 0.000, while the R-squared coefficient value is 0.609, which means that teacher performance at the Hikmatul Amanah Supreme Court is influenced by leadership style and culture. organization by 60.9% while around 39.1% is influenced by other variables outside. This study has limitations on the relatively small number of respondents, so that in the future the population can be added again.